INVESTIGATING THE EXPERIENCES AND PERCEPTIONS OF THE LGBTQIA+ STUDENTS AT ONE PUBLIC UNIVERSITY REGARDING ACCESS AND INCLUSION IN HIGHER EDUCATION IN SOUTH AFRICA - Matsoso, Teele Bernard (Nazarbayev University Graduate School of Education, 2022)
This study investigated the lived experiences of students who are identified as lesbian, gay, bisexual, transgender, queer, intersexual or asexual (LGBTQIA+) at one South African higher education institution in terms of their perceived challenges to access and inclusion. The existing literature provides different perspectives, ranging from gender identity to social justice theories, all of which point to socially unjust discrimination and marginalization of LGBTQIA+ students based on their sexual orientation status. This qualitative phenomenological study drew on the lived experiences and perceived challenges or barriers of 10 participants who identified as members of the LGBTQIA+ community in South Africa. The research was conducted using semi-structured, face-to-face interviews. Audio recordings were used for authenticity of data generated and transcription purposes. The data was coded and analyzed thematically. Findings were that the LGBTQIA+ students experienced a variety of unjustifiable challenges including non-inclusive university policies on admission and student housing; bullying and rejection by their peers; a lack of awareness and education about the community by university faculty or general workers; and overall lack of integration and socialization to help make their university experiences more successful. These challenges were largely negative and unjust because, while LGBTQIA+ people are equally protected by the same human rights as enshrined in the South African Constitution, they are constantly stigmatized and discriminated against when it comes to fully accessing and participating in higher education. Keywords: LGBTQIA+, students, higher education, access, inclusion, sexual orientation, social justice, and human rights
Keywords: LGBTQIA+; students; higher education; access; inclusion; sexual orientation; social justice; human rights; Type of access: Open Access